2013
DOI: 10.1155/2013/536081
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Pyogenic Cholangitis: Disease Characteristics and Patterns of Recurrence

Abstract: Recurrent pyogenic cholangitis (RPC) is characterized by repeated infections of the biliary system with the formation of stones and strictures. The management aims are to treat acute cholangitis, clear the biliary ductal debris and calculi, and eliminate predisposing factors of bile stasis. Operative options include hepatectomy and biliary drainage procedures or a combination of both; nonoperative options include endoscopic retrograde cholangiopancreatography (ERCP) or percutaneous transhepatic cholangiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Although non-operative treatments provide good short-term control of disease, 5,15,16 long-term outcomes are hindered by the high incidence of recurrent stones (20%-50%) and cholangitis, with biliary strictures predicting recurrence. [4][5][6]15,16 Surgical treatment of RPC generally yields better results than non-operative techniques because of removal or bypass of the diseased biliary tract along with the eradication of stones. 6 In the current study like other studies, 17,18 isolated left sided involvement was more common (49%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although non-operative treatments provide good short-term control of disease, 5,15,16 long-term outcomes are hindered by the high incidence of recurrent stones (20%-50%) and cholangitis, with biliary strictures predicting recurrence. [4][5][6]15,16 Surgical treatment of RPC generally yields better results than non-operative techniques because of removal or bypass of the diseased biliary tract along with the eradication of stones. 6 In the current study like other studies, 17,18 isolated left sided involvement was more common (49%).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]15,16 Surgical treatment of RPC generally yields better results than non-operative techniques because of removal or bypass of the diseased biliary tract along with the eradication of stones. 6 In the current study like other studies, 17,18 isolated left sided involvement was more common (49%). However, the frequency of left-sided involvement in the present study was lower than those reported by Chen et al (77%) 19 and Jiang et al (72%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations